Improvement of a grey based method for supplier selection problem - Jadidi, Omid; Mohd Yusuff, Rosnah; Firouzi, Fatemeh; Tang, Sai Hong (2008)
Purpose: In this article, we combine this new approach based on the concepts of Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to evaluate and select the best supplier. Design/methodology/approach: Supplier evaluation is a Multi-Attribute Decision-Making (MADM) problem that is affected by quantitative and qualitative factors, some of which may conflict. Since most of the input information is not known accurately, selecting the right suppliers becomes more difficult. Grey theory is one of the new mathematical methods used to analyze systems with uncertain and incomplete information. Findings: Through this article, it is demonstrated that the improved method, which is used to solve the MADM problems for selecting the best supplier, is a good means of evaluation, and it appears to be more appropriate. Practical implications: Grey theory is a new mathematical field that is one of the methods used to study the uncertainty of a system. Originality/value: Through this article, it was demonstrated that the improved method, which is used to solve the MADM problems for selecting the best supplier, is a good means of evaluation, and it appears to be more appropriate.